Building the future for national trauma research - Gregory J Jurkovich; Eileen M Bulger; Michelle A Price; Bellal Joseph; Raminder Nirula; Elliott R. Haut; Eileen Bulger; Rosemary A Kozar; Saman Arbabi; Mitchell J. Cohen; Todd W. Costantini; Marie M. Crandall; et al. (Trauma Surgery & Acute Care Open)
This paper describes the current funding, infrastructure growth and future state of trauma research. It also introduces a group of review articles generated from The Future of Trauma Research: Innovations in Research Methodology conference hosted by the American College of Surgeons Committee on Trauma in July 2019.